¿Presencia de Ireneo en el Comentario al Cantar de Gregorio de Nisa? - Nicola, Alejandro E. 1975- (2014)
The purpose of this article is to show how Ireneus of Lyon´s thought was present in one of Gregory of Nyssa´s fundamental works: Commentary on The Song of Songs. This work reflects a convergence of deep biblical reflection and the philoshophy of the time. Gregory is among the ecclesiastical writers who have commented on this beautiful love poem in the Old Testament. Even though there is no mention of the Lugdunian in the critical edition of the work, some concepts and themes may be found which help identify an influence form Ireneus on Gregory´s Commentary on the Song of Songs. These elements allow us to give relevance to the relationship between these two patristic authors, who come into contact in order to show the church´s spousal reality, which has a pneumatological-salvific dynamics, open to all mankind.
Keywords: Comentario al Cantar de los Cantares; Gregorio de Nisa; Ireneo de Lyon; Eclesiología; pneumatología